Design of terahertz CMOS integrated circuits for high-speed wireless communication - Fujishima, Minoru (The Institution of Engineering and Technology, 2019)
The book comprises of 5 chapters and covers most of our current knowledge, from the background to the design of a terahertz complementary metal oxide semiconductor (CMOS) transceiver for realizing ultrahigh-speed wireless communication.
Keywords: Metal oxide semiconductors, Complementary -- Design.; Terahertz technology.; Wireless communication systems.; elektronické knihy; electronic books